Palaeoecological Conditions in the South-Eastern and Western Baltic Sea during the Last Millennium - Ekaterina Ponomarenko; Tatiana Pugacheva; Liubov Kuleshova (Quaternary)
We present the reconstruction of palaeoenvironmental conditions in the Gdansk, Bornholm, and Arkona Basins of the Baltic Sea over the last millennium. A multiproxy study (including geochemical, XRF, grain size, AMS, and micropalaeontological analyses) of five short sediment cores was performed. The relative age of the sediments was determined based on the Pb distribution along the sediment sequences, as radiocarbon dating has resulted in an excessively old age. The retrieved cores cover two comparable warm periods, the Medieval Climate Anomaly and the Modern Warm Period, for which the increase in surface water productivity was reconstructed. Notably, the production of diatoms was higher during the colder periods (the Dark Ages and Little Ice Age), but this was also the case within the Modern Warm Period. In the Gdansk Basin, the initial salinity increase during the Littorina transgression started after 7.7 cal. a BP. The increased inflow activity was reconstructed during the Medieval Climate Anomaly, even in the Gdansk Basin, despite, in general, very low foraminiferal amounts and diversity. The strongly positive North Atlantic Oscillation Index during this period led to the prevalence of westerly winds over the Baltic region and stronger saltwater intrusions. In the recent sediments, the reconstructed inflow frequency demonstrates a variability against the reduction trend, and a general decline compared to the Medieval Climate Anomaly is seen.